A novel MPZL2 c.68delC variant is associated with progressive hearing loss in Chinese population and literature review. Issue 3 (27th May 2022) - Wang, Zhili; Jiang, Mengda; Wu, Hao; Li, Yun; Chen, Ying
Abstract: Objective: The aim of this study was to identify genetic etiology in two unrelated Chinese probands with progressive sensorineural hearing loss. Methods: Two unrelated Chinese families were recruited. Genetic etiology was identified by targeted next‐generation sequencing (NGS) and verified by Sanger sequencing. Hearing evaluations included pure tone audiometry, auditory brainstem response to clicks, and otoscopic examination. Medical history and computerized tomography scan of temporal bone were also collected. In addition, linear regression was used to summarize all of the reported cases and estimate the progression of hearing loss. Results: A 28‐year‐old man with variant c.68delC had progressive, moderately severe hearing loss and a suspicious history of renal impairment. His hearing result was 63.75 dB HL. The other proband was the youngest patient with MPZL2‐related hearing loss reported so far in the literature (genotype: c.220C>T homozygote). Her hearing result by click‐ABR was 25 dB nHL at 3 months of age, and deteriorated to 40 dB nHL at 15 months. Behavioral audiometry identified a hearing loss of 26.25 dB HL. In summarizing all of the reported cases, using linear regression, MPZL2‐related hearing loss may deteriorate by 0.59 dB HL per year, and different MPZL2 variants may lead to different rates of progression. Conclusion: In this study, we first identified two unrelated patients with MPZL2 ‐related hearing loss in Chinese population, and a novel variant c.68delC. Our results expanded the mutation spectrum of deafness genes. Further studies are required to clarify the genotype–phenotype correlation and the progression of MPZL2 ‐related hearing loss. Abstract : In this study, we first identified two unrelated patients with MPZL2‐related hearing loss in Chinese population, and a novel variant c.68delC. Our results expanded the mutation spectrum of deafness genes. Of all the biallelic MPZL2 individuals in literature, the predicted PTA [dB HL] was 38.82 + 0.59 × Age [years] (R2=0.383, p=0.0048), indicating a rate of deterioration of hearing of 0.59 dB HL per year.